Sustainable polymer-based phase change materials for energy efficiency in buildings and their application in aerial lime mortars - Frigione, M. (2020)
An experimental study aimed at investigating the possibility to produce a Phase Change Material (PCM) for mortars by incorporating through the ??form-stable method? a thermoplastic low-melting polymer (PEG 1000) into a porous inert substrate (i.e., Lecce Stone), obtained as residue from processing stone, is reported. The viscosity of pure PEG at different temperatures was first assessed to identify an appropriate processing temperature to introduce fluid PEG into the pores of the stone. A complete (chemical, thermal and morphological) characterization was performed on the developed PCM composites, varying the impregnation times. Aerial lime-based mortars were produced with the addition of the selected experimental PCM composite, taking as comparison the mortar containing only the stone as inert aggregate. On the different mortars, mechanical tests were performed in both compression and bending mode and the thermal conductivity was measured.